Microalgae extract induces antidepressant-like activity via neuroinflammation regulation and enhances the neurotransmitter system. (December 2022) - Sasaki, Kazunori; Linh, Tran Ngoc; Hirano, Atsushi; Tominaga, Kenichi; Nukaga, Sachiko; Nozaki, Hiroyuki; Arimura, Takashi; Isoda, Hiroko
Abstract: The increasing prevalence of mental disorders, such as depression, is currently a serious public health concern. Microalgae are a diverse group of organisms that contain many bioactive compounds such as polyunsaturated fatty acids and polyphenols. These compounds can exhibit many health benefits such as antioxidative, anti-inflammatory, anticancer, and anti-obesity effects. In the present study, we focused on microalgal ( Botryococcus terribilis ) extract (ME) rich in Me-meijicoccene (MM), a novel compound. Our results showed that pretreatment of SH-SY5Y cells with ME and MM ameliorated dexamethasone (depression-causing substance)-induced cytotoxicity. The results of the tail suspension test (TST) indicated that ME (50 mg/kg) induced antidepressant-like activity in TST-stressed mice. Our microarray analysis revealed that ME upregulated neurotransmitter-related gene (neurotransmitter secretion) expression and downregulated neuroinflammatory-related gene (chemokine-mediated signaling) expression in the cerebral cortex. ME also induced an increase in neurotransmitter and brain-derived neurotrophic factor levels, and a decrease in corticosterone and pro-inflammatory cytokine levels in the serum, cerebral cortex, and hypothalamus. Altogether, our study is the first to report that 50 mg/kg ME (not 100 mg/kg) exerts antidepressant-like effects via regulating neuroinflammation and modulating neurotransmitter systems in the mouse brain, highlighting the prospects of ME in the treatment of depressive disorders of a psychosocial nature.